2012
DOI: 10.1002/cphc.201100655
|View full text |Cite
|
Sign up to set email alerts
|

What Determines the Rate of Excited‐State Intramolecular Electron‐Transfer Reaction of 4‐(N,N′‐dimethylamino)benzonitrile in Room Temperature Ionic Liquids? A Study in [bmim][PF6]

Abstract: The kinetics of excited-state intramolecular electron-transfer reaction and dynamics of solvation of the intramolecular charge transfer (ICT) state of 4-(N,N'-dimethylamino)benzonitrile (DMABN) was studied in 1-butyl-3-methylimidazloium hexafluorophosphate, [bmim][PF(6)], by monitoring the dual fluorescence of the system. The picosecond time-resolved emission spectra (TRES) of DMABN exhibit decay of the locally excited (LE) emission intensity and shift of the ICT emission peak position with time, thus capturin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Samanta and coworkers also investigated the photoinduced CT of 4-(N,N 0 -dimethylamino)benzonitrile (DMABN) in ILs. 187 They found that the picosecond time-resolved emission spectrum exhibited decay of the LE state emission intensity and shift of the peak position of CT state emission with increasing time after the excitation. By analyzing the evolution of the CT state from the LE state and solvent relaxation of the CT state, they concluded that the LE -CT interconversion rate is determined not by the slow dynamics of solvation but the rate of structural reorganization of the molecule, namely, twisting around the bond between the dimethylamino and cyanophenyl moieties, which depends on the viscosity.…”
Section: Et and Ct Reactions In Ilmentioning
confidence: 99%
See 1 more Smart Citation
“…Samanta and coworkers also investigated the photoinduced CT of 4-(N,N 0 -dimethylamino)benzonitrile (DMABN) in ILs. 187 They found that the picosecond time-resolved emission spectrum exhibited decay of the LE state emission intensity and shift of the peak position of CT state emission with increasing time after the excitation. By analyzing the evolution of the CT state from the LE state and solvent relaxation of the CT state, they concluded that the LE -CT interconversion rate is determined not by the slow dynamics of solvation but the rate of structural reorganization of the molecule, namely, twisting around the bond between the dimethylamino and cyanophenyl moieties, which depends on the viscosity.…”
Section: Et and Ct Reactions In Ilmentioning
confidence: 99%
“…Meanwhile, Samanta and coworkers investigated the intramolecular ET reaction of crystal violet lactone (CVL) in several ILs and found that this ET reaction is governed by the slow solvation dynamics, which is related to the viscosity. 187 As a consequence, the intramolecular ET of CVL was difficult to occur in highly viscous ILs with long solvation times. Samanta and coworkers also investigated the photoinduced CT of 4-(N,N 0 -dimethylamino)benzonitrile (DMABN) in ILs.…”
Section: Et and Ct Reactions In Ilmentioning
confidence: 99%
“…Among many donor-acceptor substituted chromophores, the most widely studied, and the one that continues to attract research attention, is 4-(dimethylamino)benzonitrile (DMABN). 18,19 This molecule shows dual emission bands; a blue emission arising from the locally excited (LE) state and a red emission from the ICT state, the latter being highly stabilized in polar solvents. Since the first report of this interesting phenomenon by Lippert et al in 1961, 20 several models have been proposed to elucidate the occurrence of dual fluorescence and to characterize the ICT state of DMABN and other structurally related molecules.…”
Section: Introductionmentioning
confidence: 99%
“…However, many contributions to elucidating the viability of these structural models have been experimentally derived from both external [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and internal factors of the DMABN molecule, [31][32][33][34][35][36][37][38][39][40][41] and theoretical data obtained with the most sophisticated computational methods. [42][43][44][45][46][47][48][49][50][51][52][53][54] Also, this topic has been the subject of several reviews. [55][56][57][58][59] Out of these extensive readings some points of great importance towards understanding the photophysics of DMABN have been incorrectly examined, and even some assumptions are taken for granted.…”
Section: Introductionmentioning
confidence: 99%